Anesthetic Management with Epidural Analgesia in a Case of Thalassemia Intermedia - Nishith Govil; Vijay Adabala; Revanth Babu Challa; Shailesh Lohani; Intezar Ahmed (Archives of Anesthesia and Critical Care, 2019)
Thalassemia is an inherited defect in the production of globulin chains transmitted by autosomal recessive inheritance. Anaesthetic management of these patients is challenging, being associated with hypersplenism, unanticipated difficult airway and vertebral malformations, perioperative high blood pressure, systemic features of iron overload, cardiac and hepatic failure and anaemia.   In this case, we highlight the anaesthetic concerns in a child of beta thalassemia intermedia with high levels of Hemoglobin F posted for splenectomy along with cholecystectomy. To avoid need of postoperative mechanical ventilation due to low oxygen carrying capacity of blood and anaerobic metabolism during the period of surgical stress, epidural catheter inserted despite possibility of epidural hematoma or bleed because of thrombocytopenia. Patient had an enhanced recovery in term of decrease oxygen demand, decrease postoperative nausea and vomiting, early ambulation and patient satisfaction. Intraoperative epidural also decreases need of neuromuscular blocking agent and intravenous analgesia. This lead to faster awakening from anaesthesia even in the presence of decrease oxygen carrying capacity due to anaemia and acidosis (anaerobic metabolism). Use of regional anesthesia should be considered in similar cases after assessing risk and benefits for individual cases.